Factors associated with scholarly publication productivity among academic staff: case of a Malaysian public university - Dhillon, Sharanjit Kaur (Elsevier, 2015)
The importance of scholarly publications to an institute of higher learning cannot be exaggerated. Publication leads to the creation of new knowledge, increases an institution's reputation, stimulates modernization and innovation, enhance the quality of academic staff and improves the economic status of the institution. Although there has been a satisfactory level of scholarly publication production among the academic staff of Universiti Teknologi Malaysia (UTM), the targets for the key performance indicators have not been achieved as desired by the institution. It is therefore significant to thoroughly understand the influencing factors for research productivity among the university staffs. The aim of this study is to investigate the factors associated with scholarly publication productivity at UTM by determining the influence of three factors, namely personal, environmental and behavioral is associated with scholarly publication productivity among academic staff. The study uses a descriptive survey to collect all relevant data. The target population consists of academic staff of UTM and particularly those from the middle management level. The results show that all three factors had a positive influence on the scholarly publication productivity among the targeted population